Speech Delay in Children Aged 6 Years (Case Study in Paud Kasih Bunda Sigam Village, Gelumbang District, Muara Enim District - Rahmah Novianti; Lily Anggraini (Departement of Mathematics Education, 2024)
This study aims to find out the factors that cause speech delays in children, what are the impacts on children who experience speech delays, and find out how to deal with children who experience speech delays. In this study, researchers used a qualitative descriptive research method, namely a case study. Data collection techniques for this research are observation, interviews, and documentation. The results of this study are regarding delays in speaking for children aged 6 years in PAUD Kasih Bunda, Sigam Village, Gelumbang District, Muara Enim Regency. It can be concluded that there are factors that cause MR to speak late, namely: there are internal factors and external factors. Internal factors come from MR himself who is male. External factors are caused by a lack of guidance from MR's parents, MR's habit of watching television and playing gadgets, low parental education, and also because of the minimal economic status of MR's parents.